Transferring management practices to China: a Bourdieusian critique of ethnocentricity - Siebers, Lisa Qixun; Kamoche, Ken; Li, Fei (Taylor and Francis, 2015)
This paper provides a critique of the emergent theories of human resource management in China with a view to generating new theoretical insights with particular reference to Pierre Bourdieu's social theory. It reassesses the relevance of the orthodox critique of ethnocentricity and the coherence of approaches embedded in Chinese culture. With reference to six case studies of the largest retail firms, we identify two key challenges: the reliance on headquarter human resource practices that reflect an ethnocentric ethos, i.e. country-of-origin bias, and the failure to empower local managers and the problems this creates for managers expected to implement ethnocentric practices. We examine how Bourdieu's social theory sheds light on the processes by which these firms realise their strategic objectives through the complicity of local managers whose scope for resistance is constrained by the use of normative control and in part through attractive remuneration and career prospects that generate Bourdieusian capital for these managers. We conclude with some suggestions for further research.